Carbohydrate Mouth Rinse Effects on Exercise Capacity in Pre- and Postprandial States - Elie-J. M. Fares; Bengt Kayser (Journal of Nutrition and Metabolism)
Background. Oropharyngeal receptors signal presence of carbohydrate to the brain. Mouth rinses with a carbohydrate solution facilitate corticomotor output and improve time-trial performance in well-trained subjects in a fasted state. We tested for this effect in nonathletic subjects in fasted and nonfasted state. Methods. 13 healthy non-athletic males performed 5 tests on a cycle ergometer. After measuring maximum power output (Wmax), the subjects cycled four times at 60% Wmax until exhaustion while rinsing their mouth every 5 minutes with either a 6.4% maltodextrin solution or water, one time after an overnight fast and another after a carbohydrate rich breakfast. Results. Mouth rinsing with maltodextrin improved time-to-exhaustion in pre- and postprandial states. This was accompanied by reductions in the average and maximal rates of perceived exertion but no change in average or maximal heart rate was observed. Conclusions. Carbohydrate mouth rinsing improves endurance capacity in both fed and fasted states in non-athletic subjects.